1963
DOI: 10.1161/01.cir.27.6.1140
|View full text |Cite
|
Sign up to set email alerts
|

Hazard of Retrograde Aortography in Dissecting Aneurysm

Abstract: During retrograde catheterization via the femoral artery and the brachial artery, the false lumen of a dissecting aneurysm was inadvertently entered in two patients. Bilateral carotid occlusion was produced in one by the high-pressure injection of contrast material into the false passage. A method is suggested to avoid this hazard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1968
1968
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Further, there is also the risk that advancing the catheter or guidewire may cause extension of the dissection, displacement of thrombotic material, or outright perforation of the aorta 9. Previous authors have suggested that such technical issues can be circumvented by first evaluating the patient's pulses, reviewing other diagnostic imaging, and using larger sheaths and guidewires to allow better visualization and torque control 10 11.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is also the risk that advancing the catheter or guidewire may cause extension of the dissection, displacement of thrombotic material, or outright perforation of the aorta 9. Previous authors have suggested that such technical issues can be circumvented by first evaluating the patient's pulses, reviewing other diagnostic imaging, and using larger sheaths and guidewires to allow better visualization and torque control 10 11.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional coronary angiography, which is the gold standard for coronary artery visualization, is associated with certain risks. Advancement of a diagnostic catheter into the false lumen may potentially extend dissection [11]. In case of present coronary artery dissection, conventional coronary angiography may not be possible from the true lumen.…”
Section: Discussionmentioning
confidence: 99%
“…Transeptal catheterization of the left atrium has been claimed to avoid the hazards of arterial catheter techniques (Hart et al, 1963 ; Allen and Trapp, 1966), but may be dangerous rlustralasian Radiology, Vol. X V , No.…”
Section: Disclssionmentioning
confidence: 99%
“…Yet another method has been the injection of contrast on the left side of the heart, either through an atrial transseptal catheter (Hart et al, 1963 ;Allen and Trapp, 1966) or a t left ventricular puncture (Heslep and Greening,196i).…”
Section: Introductionmentioning
confidence: 99%